Comparative Analysis of Consumer Behaviour between Traditional Fish Markets and Modern Retail Outlets in Kolkata, West Bengal - Bhutia, Tenji Pem; Kumar, Vinod Kumar; Qureshi, Neha Wajahat; Ranjan Kumar, Nalini; Nath Ojha, Shekhar (Fishery Technology, 2020)
The present study was conducted in Kolkata, toexamine if there is any difference in consumerbehavior from traditional fish markets to modern fishmarkets. The survey included 300 households, 150each from the traditional fish markets and modernretail outlets. The perception study showed that 49,70 and 61% of the respondents perceived quality,variety and price of fish as good, plenty and reasonable,respectively in traditional fish markets, while67, 53 and 49% of the consumers perceived quality,variety and price as average, very few and very highrespectively in modern retail markets. Perceptionindex score revealed that 82.67% had perceivedtraditional market as good (>0.66) in the context ofquality, variety and price, while modern retail outletsare perceived poor, (